Dinamika Komunikasi Perempuan Fatherless dengan Ayah Penyandang Gangguan Mental di Kota Garut - Syahnaz Apriliza Putry; Ummu Salamah; Ismira Febriani (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to understand the interpersonal communication patterns of fatherless women whose fathers exhibited signs of mental illness within the cultural framework of the Sundanese community. Utilizing a transcendental phenomenological approach, qualitative data were collected through in-depth interviews with four informants who had experienced emotional absence and communication breakdown with their fathers during childhood. The findings reveal that persistent emotional absence and dysfunctional communication in the father-child relationship created significant barriers to openness, contributed to emotional regulation difficulties, and fostered unhealthy attachment styles in adult romantic relationships. Family communication manifested as one-directional, closed, or emotionally tense interactions—reflecting the five dimensions of interpersonal communication theory by Joseph A. DeVito. Psychological insights confirm that unresolved early emotional wounds influence relational dynamics in adulthood. This study contributes to communication scholarship by highlighting the intersection of cultural values and family communication structures in shaping emotional resilience. It underscores the critical role of emotional presence and open dialogue within familial and cultural systems as protective factors for the psychological well-being of fatherless women. Implications for culturally sensitive family interventions and research directions are discussed.